Pathology of Melanocytic Nevi and Malignant Melanoma - Barnhill, Raymond L.; Piepkorn, Michael; Busam, Klaus J. (Springer New York, 2004)
Highly acclaimed and considered the leading reference in the field, Pathology of Melanocytic Nevi and Malignant Melanoma has now been fully revised and updated to accomodate rapid advances in the field of melanoma pathology. Drs. Michael Piepkorn and Klaus Busam have now joined Dr. Barnhill, world-renowned expert in dermatology and pathology, to expand the text with new sections on the genetics and cytogenetics of melanoma, sentinal lymph node biopsy, the new AJCC TNM staging system for melanoma, the mechanisms of melanoma metastasis. The successful focus and format of the first edition have been preserved. Each lesion and diagnosis is clearly illustrated, now with more than 340 new, digitally enhanced full-color photomicrographs and over 125 tables. A corresponding precis, or concise description of the clinical features, histopathology, differential diagnosis, and outstanding characteristics of each lesion provides readers with a quick yet comprehensive overview of each topic covered. With the inclusion of recent advances in cancer research and new techniques, the second edition of Pathology of Melanocytic Nevi and Malignant Melanoma is the essential reference for every practicing dermatopathologist, pathologist, dermatologist, and cancer research scientist today